Pendidikan Seks bagi Anak dan Remaja: Perspektif Psikologi Islam - Nelly Marhayati (JURNAL ILMIAH SYI'AR, 2021)
There are still many people who think that sex education is taboo, forbidden, and even something that is disgusting to talk about, especially in children and adolescents. In general, the purpose of sex education should be able to prevent the occurrence of sexsual criminal acts. Such as sexsual harassment, pregnancy outside of marriage and even abortion. It is the same with the purpose of sex education in islam is to maintain the safety and honor and sanctity of our children in the midst of society. According to psychology introduce sex education as early as possible for the child is better. Islam actually had to explain about sex education in the Qur’an and Sunnah. Where explained that sex education is not something  that is taboo and should start from young children. The important thing to remember when giving sex education is to be in accordance with the child’s age and level of intelligence. In this paper will be presented on several ways to teach sex education in accordance with Islamic psychology perspective.